Design Of Solar Powered Drainage Cleaning Machine - et. al., Periyasamy R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In India removal of the solid waste is a significant issue, as per the sources 80% of solid waste is arranged in seepages, stream, lake and other water bodies. The solid waste like plastic containers, polythene packs, soda pop jars, solid pieces and so forth, are generally stream with these lines which need to channel stage to arrange. In any case this solid waste can cause blockage of these lines which will in general flood like circumstance in blustery season. To keep away from this sort of circumstances this waste is should have been removed from the seepage for persistent progression of waste water. Waste can be spotless utilizing programmed mechanical framework rather than manual robots and work. The chief function of the proposed model is to gather solid waste from seepage framework and gather it in bucket. This framework will chip away at sun based energy so it very well may be use where power will be inaccessible. The filtration is done completely by mechanical method. This will diminish the issue looked in manual waste cleaning. This framework will assist with diminishing sicknesses causes because of the sewage water like jungle fever, Dengue, typhoid, etc..